Innovating Empirical Research on Legitimacy: Repertory Grid Analysis - Osterberg-Kaufmann, Norma (Frontiers in Political Science, 2022)
This article uses a study on the impact of political (EU-specific) knowledge on perceptions of the legitimacy of the European Union to demonstrate the potential of the repertory grid method in the social sciences. The first objective of the study is methodological. The aim is to test the added value of the repertory grid method for surveying attitudes toward contested concepts, such as legitimacy. To this end, the influence of political knowledge on the perception of the legitimacy of the European Union is surveyed with the help of repertory grid interviews. Second, possible research questions on the effect of political knowledge on perceptions of legitimacy are developed, using the results of the present repertory grid study as a guidepost in this still underdeveloped field of research. The data collected in this preliminary study provide evidence that the importance of democratic norms and values for the evaluation of the legitimacy of national and European institutions is increasing, but at the same time critique of the political system is also increasing and the perception of legitimacy is thus decreasing.